Band structure and density of states in the normal state of FeSe, Fe2Se2, Fe2Se1 and Fe2SeTe superconductors - Lin, T.Y.; Kassim, H.A.; Shrivastava, K.N. (Elsevier, 2010)
We have calculated the band structure of FeSe. FeSe from which 2 atoms of Se out of 4 per unit cell have been removed and a system in which 2 Te atoms have been substituted for 2 Se atoms in a unit cell in the normal state. In all of the cases the Fermi energies cross multiple bands and there is always at least one conduction band minimum whose energy is lower than the valence band maximum. Hence, on the basis of the calculated band structures, these systems have no semiconducting band gap and should behave as metals. Similarly, there is non-vanishing density of states at the Fermi level. Large effects are found in the density of states. The normal state gap reduces in the composition which becomes superconducting. (C) 2010 Elsevier B.V. All rights reserved.